2009
DOI: 10.1111/j.1440-1630.2008.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of cognitive problems in schizophrenia and implications for vocational functioning

Abstract: Occupational therapists need to have a good understanding of the profile of cognitive problems among people with schizophrenia, in order to tailor our intervention according to their cognitive strengths and difficulties. Several cognitive remediation strategies and programs have been designed specifically for people with mental illness. Equipping ourselves with skills in conducting such programs will augment our expertise in vocational rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 85 publications
4
20
0
1
Order By: Relevance
“…Our results suggest that social skills training may be an important intervention in addition to compensatory strategies, such as accommodating the social work environment, for increasing working hours per week among IPS-service users with social disabilities. This concurs with previous research (14,24) and also in particular with Cheung and Tsang (25), who found that social skills were most easily taught after a person had gained employment where the context was clearly defined. Furthermore, the same authors found that social skills training at work enhanced employment outcomes among people with SMI in psychiatric rehabilitation in general, which has also been shown in systematic reviews of the research literature (1,26).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that social skills training may be an important intervention in addition to compensatory strategies, such as accommodating the social work environment, for increasing working hours per week among IPS-service users with social disabilities. This concurs with previous research (14,24) and also in particular with Cheung and Tsang (25), who found that social skills were most easily taught after a person had gained employment where the context was clearly defined. Furthermore, the same authors found that social skills training at work enhanced employment outcomes among people with SMI in psychiatric rehabilitation in general, which has also been shown in systematic reviews of the research literature (1,26).…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that CPT could predicted everyday living skill deficits. This finding was supported by Erlenmeyer-Kimling, Rock, Roberts, Janal, Kestenbaum, Cornblatt (2007), Fujii, Wylie and Nathan (2004), Oie, Sundet, and Ueland (2010), Puig, Penade, Gasto, Catalan, Torres, Salamero (2008), Ritsner (2007) and Tan (2009).…”
Section: Discussionsupporting
confidence: 55%
“…First, the cerebral activations linked to motor readiness were shown to disturb the acquisition of resting state signals (Baz an et al, 2015). Second, the reliability of this method was questioned due to the poor insight and executive dysfunctions that may exist in patients with schizophrenia (Tan, 2009). Finally, activity related to AVHs may precede the button press (Diederen et al, 2010) and exhibit complex dynamics (Lefebvre et al, 2016).…”
Section: Introductionmentioning
confidence: 99%